Adaptation and validation of a Self-Efficacy Scale for Physical Activity Practice – SESBC Scale - Walan Robert da Silva; Cinara Sacomori; Thiago Emannuel Medeiros; Tailine Lisboa; Kamyla Thais Dias de Freitas; Fernando Luiz Cardoso (Revista Brasileira de Atividade Física e Saúde)
The present study aimed to perform the translation, cross-cultural adaptation, and construct validation of the Self-Efficacy Scale based on the Stages of Behavior Change for Physical Activity Practice (SESBC), and also to test its internal consistency and reproducibility. The scale, composed of 20 items, was adapted to the Brazilian reality using the technique of back-translation. In empirical terms, construct validation and the internal consistency of the instrument were tested in 281 state public servant technicians of both sexes, older than 18 years, while reproducibility was tested in 91 university students. In the exploratory factor analysis, the 19 items loaded onto one single factor, and factor loadings varied from 0.41 to 0.88, explaining 52.7% of the total variance of the subjects’ responses. e SESBC showed good reliability in terms of internal consistency (alpha of 0.94) and good reproducibility in terms of test and re-test (ICC < 0.40-0.80) after two weeks. Of the 19 items, 17 presented ICC > 0.60. Therefore, the SESBC reached adequate levels of validity, internal consistency and reproducibility and can be used to measure self-efficacy for physical activity practice.